2012
DOI: 10.1021/bi201738a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Functional Analysis of HIV-1 Vif Oligomerization

Abstract: HIV-1 Vif is an accessory protein that induces the proteasomal degradation of the host restriction factor, apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3G (APOBEC3G). The N-terminal half of Vif binds to APOBEC3G and the C-terminal half binds to subunits of a cullin-5-based ubiquitin ligase. This Vif-directed ubiquitin ligase induces the degradation of APOBEC3G (a cytidine deaminase), and thereby protects the viral genome from mutation. A conserved PPLP motif near the C terminus of Vif is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
2
6
1
Order By: Relevance
“…This interpretation would be consistent with previous studies using purified Vif protein (45); however, it has to be taken with caution as the residual FRET efficiency is rather close to the significance limit (62). On one hand, a very recent study also pointed out the involvement of domains such as the HCCH motif, the BC box, and downstream residues (S165 and V166) in the oligomerization property of Vif (58). This could explain the interaction observed by co-IP between the eGFP-Vif AALA mutant and wild-type HA-Vif (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This interpretation would be consistent with previous studies using purified Vif protein (45); however, it has to be taken with caution as the residual FRET efficiency is rather close to the significance limit (62). On one hand, a very recent study also pointed out the involvement of domains such as the HCCH motif, the BC box, and downstream residues (S165 and V166) in the oligomerization property of Vif (58). This could explain the interaction observed by co-IP between the eGFP-Vif AALA mutant and wild-type HA-Vif (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…3B, middle panel, compare lanes 4 and 3), suggesting the Vif AALA protein partially lost its capacity to form multimers. This result is consistent with previous observations indicating that regions outside the PPLP motif also participate in Vif oligomerization (58). Indeed, although the AALA mutation impaired oligomerization (36,44,45; this study), dimerization of the protein was still observed in vitro (45) and could be sufficient to be detected by immunoprecipitation.…”
Section: Expression Of Egfp-and Mcherry-vif Fusion Proteinssupporting
confidence: 94%
“…Previous reports indicated Vif to be oligomeric in solution but our findings suggested it formed a discrete, well-ordered monomeric complex when bound by CBFβ and ELOBC (Auclair et al, 2007; Marcsisin and Engen, 2010; Paul et al, 2006; Techtmann et al, 2012) (Figure 1). To determine if assembly with CUL5/RBX2 caused a major change in oligomerization or conformation of the Vif substrate receptor, we performed SEC-MALLS and SAXS analysis on the CRL5-Vif-CBFβ complex.…”
Section: Resultscontrasting
confidence: 59%
“…Importantly, the disruption of Vif oligomers was shown to increase the amount of packaged A3G in budding virions, which was associated with a marked reduction in HIV-1 infectivity [14]. The contribution of the PPLP motif to Vif oligomerization is supported by an abundance of biophysical analyses, including size-exclusion chromatography [16], dynamic light scattering [16], analytical ultracentrifugation [17], small-angle X-ray scattering [18], and chemical crosslinking mass spectrometry [19]. Furthermore, PPLP-dependent oligomerization of Vif was also shown in the context of living cells by fluorescence lifetime imaging microscopy (FLIM) [20].…”
Section: The Pplp Motif and Oligomerization Of Vifmentioning
confidence: 99%
“…Its location does not support the hypothesis that Vif oligomerizes through direct interaction between PPLP motifs of adjacent Vif moieties. In fact, mutation of PPLP-to-AALA reduced, but did not obliterate oligomerization [16,17]. Vif oligomerization mediated through regions other than the PPLP motif have been reported [16], including the zinc-binding domain [24], the N-terminal half, and the intrinsically disordered C-terminal end of Vif [19].…”
Section: The Pplp Motif and Oligomerization Of Vifmentioning
confidence: 99%